The Japanese sense of beauty - Takashina, Sh?uji 1932- (Japan library (Shuppan Bunka Sangy?o Shink?o Zaidan))
The Japanese sense of beauty is an important contribution to the study of aesthetics and cultural history, offering insights that will change the way you think about Japanese art.